Lean Manufacturing and Manufacturing Cycle Effectiveness Analysis of the Fabrication Process for the PT Pou Yuen Workshop Construction - Zahid Karim Hanifan; Thomas Sukardi (Journal of Applied Mechanical Engineering Innovation, 2025)
This study aims to increase production effectiveness in the fabrication process for the PT Pou Yuen Indonesia workshop construction by applying Lean Manufacturing and Manufacturing Cycle Effectiveness (MCE). The research used a quantitative descriptive method by taking representative samples from the overall production process in the cutting, setting, and submerged arc welding (SAW) lines. Data were collected through interviews, observation, documentation, and measurements of process time and transfer distance. The results show that the most effective cutting method is the method used by MSS, which applies a double-nozzle cutting process. In the setting process, the most effective methods are those used by MKR and MSS because they require fewer workers and have shorter process times than SST. In the welding process, the most effective method is the method used by MKR because flux is supplied during the welding process. Several types of waste were identified, including waiting time, transportation waste, inventory waste, motion waste, and processing waste. Applying the recommended process methods can reduce the total production process time by 9,011.99 seconds for one WF beam and reduce transfer distance by 2,070 m.